THE SYSTEMATIC REVIEW OF OPEN VERSUS LAPAROSCOPIC SURGERY IN THE MANAGEMENT OF PATIENTS WITH GALLBLADDER CANCER - Ade Ansari, Witia; Putri Handayani, Sri; Febriana, Dita; Utami, Deviani; Wirawan, Ahmad (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Gallbladder cancer (GBC) is a rare highly aggressive disease with a global prevalence of 2/100000 people, with women being 2-3 times more likely than men. Management requires a multimodal strategy, with surgery being the gold standard for curative intent. Nowadays, treating common gastrointestinal cancers with laparoscopic techniques is commonly recognized. However, there is still debate on the laparoscopic method for treating GBC. The aim: This study aims to show the differences between open and laparoscopic surgery for gallbladder cancer. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like PubMed and ScienceDirect, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Results: In the PubMed database, the results of our search brought up 22 articles, whereas the results of our search on ScienceDirect brought up 85 articles. The results of the search conducted by title screening yielded a total 17 articles for PubMed and 12 articles for ScienceDirect. We compiled a total of 22 papers, 11 of which came from PubMed and 11 of which came from ScienceDirect. We excluded 3 review articles, 4 duplicate articles, 4 non-full text articles, 2 articles having ineligible subjects, and 1 article having insufficient outcomes. In the end, we included eight research that met the criteria. Conclusion: The outcomes of laparoscopic and open surgery in the management of gallbladder cancer are comparable in terms of post-operative complications, recurrence rates, survival rates, and disease free survival rates. However, laparoscopic approach shows benefit on length of hospital stay